Pengaruh Gaya Kepemimpinan, Komunikasi, dan Keseimbangan Lingkungan Kerja terhadap Kinerja Pegawai Puskesmas Sumobito Jombang - Fina Febriyanti; Lailatus Sa'adah; Akhmad Taqiyuddin (Yayasan Literasi Sains Indonesia, 2026)
The purpose of this research is to examine the impact of leadership style, communication, and work environment on employee performance at Sumobito Public Health Center, Jombang, both individually and in combination. Human resource management's foundational role in enhancing community healthcare service quality is the study's theoretical underpinning. The researchers used a quantitative method in this study by surveying workers and seeing them in action. Using a purposive sample approach, 62 respondents were chosen for the research. Multiple linear regression analysis was used to examine the data. There was no statistically significant relationship between leadership style and worker output. There was a substantial relationship between communication and employee performance, with communication playing a more central role. Workers are more likely to be productive and satisfied in their jobs when there is open communication and a positive work atmosphere. At the same time, the leadership style, communication, and work environment all had a big role in how well employees performed. According to the results, the two most important aspects of the work environment and communication at Sumobito Public Health Center that contribute to the enhancement and long-term management of employee performance are these two elements.